LANDSCAPE GOVERNANCE: A REVIEW OF ASSOCIATED LANDSCAPE REGULATIONS IN MALAYSIA - Mohd Zulhaili Teh,; Suhardi Maulan,; Mohd Sallehuddin Mat Noor,; Shamsul Abu Bakar,; Marina Abdullah, (Journal of Islamic, Social, Economics and Development, 2024)
Malaysia is environmentally rich and blessed with beautiful landscapes. With the increase in the efforts of landscape beautification this country, surprisingly, there are no landscape regulations that directly govern the landscaping work. Generally, there are several regulations which are observed by landscape practitioners that help to manage and govern landscape development, conservation, and preservation. Nevertheless, these laws and policies have not been properly implemented due to some issues such as lack of coordination, and weak enforcement. Such predicaments can cause inefficiency in landscape development and protection. This study will examine acts related to landscape development process in Malaysia. Another objective of this research is to identify the category of relationship to the landscape. Finally, the researcher also would like to analyze the implementation of these acts in the landscape development in Malaysia. These acts' potentialities and constraints of the environmental laws and policies in Malaysia consist of 25 acts in different categories. Several acts related to the landscape such as Act 172- Town and Country Planning 1976, Act 226 - National Park Act 1980, the 474 - Land Development Act 1956, Act 171 - Local Government Act 1976, etc; have also been implemented to manage landscape development in the country. The finding of this research focuses on the relationship between ‘landscape’ and the legislative approach with regard to the current landscape regulations practices. Other than that, this research finding also contributes to the understanding of these regulations and their limitations.